Efektivitas Penggunaan Rompi Pijat Oksitosin Otomatis untuk Memperlancar dan Meningkatkan Produksi ASI - Desriyanti Desriyanti; Rhesma Intan Vidiastary; Elmie Mufitana; Muhammad Arsyad Ardiansyah; Alfina Sofianawati; Fadhilah Nurul Karimah (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Breast milk is nutrition for newborns, where exclusive breastfeeding will be given to babies until they are six months old. The hormone oxytocin can affect the production of breast milk. The release of the hormone oxytocin is carried out by a stimulation of the nipples through baby sucking or massage where breast massage is called breast message which can be done by a mother, or with the help of a special massage clinic to facilitate breastfeeding. The author created an Automatic Oxytocin Massage Vest to Accelerate Breast Milk Production in Breastfeeding Mothers. The strategy for implementing the vest tool can be used by the community, and knowing the level of usefulness of the tool. The next step will be knowing the effectiveness of the implementation of the vest using the "One Groups Pretest-Posttest Design" method, namely a research design that has a pretest before being given treatment and a posttest after being given treatment. Based on the results of the respondents and the analysis that has been carried out, it will be concluded that the hormone oxytocin is a hormone that has an important influence on the production of breast milk in nursing mothers, oxytocin massage tools are effective in increasing milk production in breastfeeding mothers, it is proven by 60% of the results of expressing breast milk from respondents more look at using an oxytocin massager. The reduced production after using the tool is influenced by several factors, including stress when using the tool and adding formula milk to babies during exclusive breastfeeding.